Cloth simulation / Nor Azlina Mohamad Salleh - Nor Azlina, Mohamad Salleh (2004)
With cloth simulation, as in most of Computer Graphics, the challenge lies in making the artifact on the screen look realistic. In particular, the cloth's movements and interactions with its surroundings ought to look familiar to the viewer, who should even be able to recognize different types of cloth simply by watching the simulation's behaviour. In the literature, realistic cloth movement has been obtained using a network of particles connected by springs (in that case, the system is referred to as a massspring system) or other natural forces. With such a model, perturbations at one cloth vertex are propagated to the other areas of the cloth as dictated by the system of differential equations that links the forces acting on all the particles. Any cloth simulation system needs efficient numerical methods for integrating the equations that describe the mechanical behaviour of the discrete representation of the cloth. Choosing the adequate method should be done with full knowledge of the advantages and weaknesses of the main techniques. Most simple simulators use explicit integration, which is easy to implement and fairly fast for small pieces of cloth. Freecloth uses implicit integration, which is harder to implement but gives much better results for large pieces of cloth. Implementation was done in OpenGL. It has been compiled on Linux and under Windows, and it should be straightforward to port to other operating systems.